FAKTOR YANG BERHUBUNGAN DENGAN PENYEMBUHAN LUKA JAHITAN PERINEUM PADA IBU POSTPARTUM DI KLINIK HJ. DERMAWATI MEDAN - Afrahul Padilah Siregar (Maternity and Neonatal : Jurnal Kebidanan, 2021)
Perineal wounds in postpartum maternal occurs in almost all first deliveries and not infrequently also in subsequent deliveries. The purpose of this study was to determine the factors associated with perineal wound repair healing in postpartum maternal at Hj. Dermawati Clinic in 2020. This research was an analytic survey with a cross-sectional approach. The population in this study were all postpartum maternal with perineal wounds repair. The sampling technique in this study was the total population technique and the measuring instrument used was a questionnaire. The results obtained were that there was a relationship between knowledge and perineal wound repair healing p = .017<.05, there was a relationship between perienum wound care and perineal wound repair healing with p = .004<.05 and there was a relationship between nutritional status and perineal suture wound healing p = .035<.05. this study is variables of knowledge, perineal wound care and nutritional status have a relationship with perineal wound repair healing in post partum maternal. It is need to educate postpartum maternal regarding the importance of treating perineal wounds and the nutritional needs of postpartum maternal